CAPITAL MARKET’S REACTION AND POLITICAL EVENTS IN INDONESIA. - IntanEka Putri S., Nurul WahidatunNisa & Lukman Hakim* (International Journal of Research Science and Management, 2018)
Certainly, the capital market has a high risk, especially in political risk. In investing their money, Investors can do it at their home or abroad. Therefore, political conditions need to be cautioned by investors, because it can affect the stock prices. The purpose of this study is to examine the influence of political events on capital market reaction in Indonesia. The approach in the formulation of this study uses literature studies by collecting and comparing literature derived from journals, articles, and news related to political events. The result of the formulation of this paper indicates that political events (presidential election and reshuffle of presidential cabinet - Kabinet Indonesia Bersatu) can influence the capital market, proven with changes in abnormal return and stock trading activity.